Relation of high neuroticism with increased methylation of the BDNF gene - Shirata, Toshinori (Neuropsychiatr Dis Treat, 2018)
BACKGROUND: Brain-derived neurotrophic factor (BDNF) is a neurotrophin that has an important function in neuroplasticity and neuronal development. It is suggested that increased methylation of the BDNF gene resulting in decreased BDNF activity is associated with depression. Meanwhile, neuroticism is a well-known risk factor for developing depression. In the present study, the relationship between methylation of the BDNF gene and personality traits including neuroticism was examined. SUBJECTS AND METHODS: The subjects were 98 healthy Japanese. Methylation levels of the BDNF gene were determined by the bisulfite-pyrosequencing method. Personality traits including neuroticism were assessed by the NEO Personality Inventory-Revised. RESULTS: There was a positive correlation between neuroticism scores and methylation levels of the BDNF gene. The subjects with higher neuroticism scores had higher levels of BDNF gene methylation compared with those with lower neuroticism scores. Meanwhile, other personality traits were not associated with BDNF gene methylation. CONCLUSION: The present study suggests that high neuroticism is related to increased methylation of the BDNF gene.